The Stability of the Simple Reaction Time - Kolesarić, Vladimir (Array, 2007)
Some of the most widely used criterion variables in psychology are simple and choice reaction time. While stability of choice reaction time as a dependent variable seems to be investigated by researchers, no such data could be found for simple reaction time measurements. The aim of this study was to determine stability of simple reaction time (SRT) in conditions in which, apart from the repeated measurements itself, no other independent variables were introduced. The experiment was conducted during 47 consecutive days of measurements, using three-level intensity of visual stimuli. Frequency of measurements, duration of the break period and time of the day when measurements were done were varied. Each day, three identical blocks of stimuli were presented to the subjects, for each of the intensity levels. Results of the daily measurements were plotted as a function of reaction time in order of stimuli presentation, and differences in the variability between blocks were observed. No effects of time of the day, frequency of measurements, or duration of the break period on SRTs stability were found for any of the intensity levels. Results seem to be homogeneous, with no observable trends. In conclusion, simple reaction time repeated measurements seem to be stable in the course of time.